PCF-Cavity FBG Fabry-Perot Resonator for Simultaneous Measurement of Pressure and Temperature - Ali, M.M.; Islam, M.R.; Lim, K.S.; Gunawardena, D.S.; Yang, H.Z.; Ahmad, Harith (Institute of Electrical and Electronics Engineers (IEEE), 2015)
In this paper, we propose a Photonic Crystal Fiber (PCF)-cavity fiber Bragg grating (FBG) Fabry-Perot resonator for simultaneous sensing of temperature and pressure. The proposed device is constructed by splicing a 1.5-mm long PCF segment between two identical saturated FBGs written in SMF-28 forming an FBG-PCF-FBG configuration. As a result, a resonance dip is created within the Bragg reflection curve. Taking advantage of the difference in pressure sensitivities between the two types of fiber, the discriminative measurement of pressure and temperature can be achieved from the shifts of the resonance wavelength and band-edge wavelength. In addition, the same temperature sensitivity of PCF and SMF-28 provides the convenience of eliminating the temperature variable and achieving temperature insensitive pressure measurement.